Study and Characterization of Tribofilm based on Activated Carbon-Nanochitosan Modified with Silicone Oil for Application of Self-Healing Coatings on Metal Surfaces - Sembiring, Sarah Mutiara; Humaidi, Syahrul; Riana, Martha (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2023)
A tribofilm material based on activated carbon and nanochitosan modified with silicone oil has been prepared using the sol gel method with variations in the composition of activated carbon at a mass ratio of 40% wt – 60% wt at 5% wt intervals. Sampling was carried out in two stages. The first stage of the synthesis of activated carbon from palm shells using activation of 7% H3PO4 and nanochitosan derived from shrimp shells using the ionic gelation method. The second stage was mixing the tribofilm material of activated carbon, nanochitosan and silicone oil using the sol gel method to produce a film-forming solution which was then characterized including: physical, chemical, mechanical and thermal properties. The characterization results showed that the most optimum composition was the tribofilm material of activated carbon/nanochitosan/silicone oil in S1 with a mass ratio of 40%wt activated carbon which produced a density of 0.94 x 103 kg/m3, a viscosity of 28.42 cP, and a liquid surface tension of 63.5 mN/m. While the performance characteristics of the metal surface coating produce a surface roughness of 0.162 µm for aluminum metal and 0.156 µm for copper metal, friction coefficient 0.024, wear rate 0.19 mm, thermal conductivity 0.092 W/m.K, corrosion properties 1a (slight tarnish), rate corrosion rate of 2.34 mm/yr in 3.5% NaCl medium, 4.33 mm/yr in seawater medium and 11,476 mm/yr in 3% H2SO4 medium and has good self-healing properties for 3 days on carbon steel metal surfaces with corrosion scratch treatment on 3.5% NaCl media, namely almost all the scratches/cracks covered due to frictional force from galvanic corrosion with active carboxyl, amine and hydroxyl groups with the healing agent aminopropyl siloxane (NH2-R-NH-Si-O-R) which reacts with metal ion particles (M-OH) in the formation of polymer chains for new network layers.